Solar Augmentation of Process Steam Boilers for Cogeneration - Rwezuva, Onekai Adeliade (Department of Mechanical Engineering, 2021)
In this study, the techno-economic feasibility of converting an existing process steam plant into a combined heat and power plant, using an external solar thermal field as the additional heat source was studied. Technical feasibility entailed designing a suitable heat exchanger, which uses hot oil from the solar field to raise the steam conditions from dry saturated to superheated. The solar field was sized to heat a selected heat transfer fluid to its maximum attainable temperature. A suitable turbine-alternator was chosen which can meet the required plant power demand. For this to be a success, the processes which require process steam were analysed and a MathCAD model was created to design the heat exchanger and check turbine output using the equations adapted from various thermodynamics and power plant engineering texts, together with the Standards for the Tubular Exchanger Manufacturer's Association. The U.S. National Renewable Energy Laboratory system advisor model was used to size the suitable solar field. A financial model was developed in Excel to check the economic feasibility of the project, using discounted payback period as the economic indicator. It was found out that amongst loan interest rates, variation of system output and the electricity output, the profitability of the project was largely influenced by the electricity tariff. An optimum size for the heat exchanger of 30ft was established from the sensitivity analysis and it was concluded that the project is currently not economically viable on an independent investor financing model, unless either the electricity tariff improves or the solar thermal energy and turbine technology costs decrease.